Vestibular migraine: epidemiology, pathogenesis, clinical picture, diagnosis and treatment - A. A. Kulesh; V. A. Parfenov (Неврология, нейропсихиатрия, психосоматика, 2022)
The epidemiology of vestibular migraine (VM), which is the most common cause of episodic dizziness, is discussed. The pathogenesis schematic is discussed, the key feature of which is the disturbance of the interaction of trigemino-vascular system, nociceptive centers of the brain stem, thalamocortical networks and the vestibular system. The clinical picture of the disease is presented in the form of spontaneous, positional, visually induced and head movement-induced dizziness, cochlear and other symptoms. The relation of vestibular symptoms and headache was analyzed. The data of neurological and vestibular examination are reflected, the features of positional nystagmus are considered in detail. The diagnostic criteria of the disease are presented. Approaches to VM attacks relief and prevention are considered.